Social Self-Esteem and Fear of Missing Out Towards the Social Media User of Generation Z - Astrid Lingkan Mandas; Khoirotus Silfiyah (Pusat Studi Bahasa dan Publikasi Ilmiah, 2022)
Social media gives many advantages, especially in making people connected to each other, but it is also admitted that the advantages have their own sinister side. Social media may also create dystopia, besides utopia, meaning that it can also be considered a bad thing, rather than good. One of the dystopias that may be found is that it also creates fear of missing out on the person that uses social media. Fear of missing out (FoMO) is a form of fearfulness and uneasiness of the person that one may miss something exciting and the feeling of constantly needing to be connected with other people. Fear of missing out is also triggered by the need to fulfill the need for self-esteem, especially social self-esteem. Social self-esteem is the social self of the people that construct self-evaluation in a certain social situation. This research aims to study the correlation between social self-esteem and FoMO. This research utilizes quantitative methods. The result of product-moment analysis shows a significant negative correlation between social self-esteem and FoMO (rxy = -0,547 to p = 0,000). Based on the result, it can be concluded that the lower the individual social self-esteem, the higher the inclination to feel the fear of missing out. Generation Z or the post-millennial generation has a quite high tendency to feel the fear of missing out due to several characteristics of this generation which have been the base of the construction of the fear of missing out, such as under-influence, being always connected, and digital intuitiveness.